Effect of handedness on fMRI activation in the medial temporal lobe during an auditory verbal memory task - Cuzzocreo, Jennifer L. (Wiley Subscription Services, Inc., A Wiley Company, 2008)
Several studies have shown marked differences in the neural localization of language functions in the brains of left‐handed individuals when compared with right‐handers. Previous experiments involving functional lateralization have demonstrated cerebral blood flow patterns that differ concordantly with subject handedness while performing language‐related tasks. The effect of handedness on function in specific stages of memory processing, however, is a largely unexplored area. We used a paired‐associates verbal memory task to elicit activation of neural areas related to declarative memory, examining the hypothesis that there are differences in activation in the medial temporal lobe (MTL) between handedness groups. 15 left‐handed and 25 right‐handed healthy adults were matched for all major demographic and neuropsychological variables. Functional and structural imaging data were acquired and analyzed for group differences within MTL subregions. Our results show that activation of the MTL during declarative memory processing varies with handedness. While both groups showed activation in left and right MTL subregions, the left‐handed group showed a statistically significant increase in the left hippocampus and amygdala during both encoding and recall. No increases in activation were found in the right‐handed group. This effect was found in the absence of any differences in performance on the verbal memory task, structural volumetric disparities, or functional asymmetries. This provides evidence of functional differences between left‐handers and right‐handers, which extends to declarative memory processes. Hum Brain Mapp 2009. © 2008 Wiley‐Liss, Inc.